2019
DOI: 10.1021/acschembio.8b01058
|View full text |Cite
|
Sign up to set email alerts
|

Salinipeptins: Integrated Genomic and Chemical Approaches Reveal Unusual d-Amino Acid-Containing Ribosomally Synthesized and Post-Translationally Modified Peptides (RiPPs) from a Great Salt Lake Streptomyces sp.

Abstract: Analysis of the full genome of an environmentally unique, halotolerant Streptomyces sp. strain GSL-6C, isolated from the Great Salt Lake, revealed a gene cluster encoding the biosynthesis of the salinipeptins, d-amino-acid-containing members of the rare linaridin subfamily of ribosomally synthesized and post-translationally modified peptides (RiPPs). The sequence organization of the unmodified amino acid residues in salinipeptins A–D (1–4) were suggested by genome annotation, and subsequently, their sequence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 31 publications
3
67
0
Order By: Relevance
“…The planar structure of 1 confirmed the dehydration of genetically encoded Ser‐1, Ser‐2 and Thr‐18 and the subsequent addition of Cys‐5 and (decarboxylated) Cys‐23 to the transients Dha‐1 and Dhb‐18 respectively (to ultimately originate the N‐terminus Lan and the C‐terminus AviMeCys rings) (SI, Figure S48). The biosynthetic origin of AviMeCys in 1 is therefore the same as that described for lanthipeptides and lipolanthines, and different to that reported for linaridins, in which the AviCys is formed between two cysteine residues …”
Section: Figuresupporting
confidence: 49%
See 1 more Smart Citation
“…The planar structure of 1 confirmed the dehydration of genetically encoded Ser‐1, Ser‐2 and Thr‐18 and the subsequent addition of Cys‐5 and (decarboxylated) Cys‐23 to the transients Dha‐1 and Dhb‐18 respectively (to ultimately originate the N‐terminus Lan and the C‐terminus AviMeCys rings) (SI, Figure S48). The biosynthetic origin of AviMeCys in 1 is therefore the same as that described for lanthipeptides and lipolanthines, and different to that reported for linaridins, in which the AviCys is formed between two cysteine residues …”
Section: Figuresupporting
confidence: 49%
“…Furthermore, an unprecedented N , N ‐dimethyl lanthionine system (NMe 2 Lan) was found to be present in 1 , based on the characteristic chemical shifts in the HSQC and the key cross‐peaks in the HMBC spectrum (SI, sections 2.3 and 2.11; Figure S28). Thus far, the N‐terminus dimethylation has been reported only for the rare linaridin family, whose members lack lanthionine rings. The involvement of a dimethylated N‐terminus in a Lan ring (NMe 2 Ala‐S‐Ala) is reported here for the first time within RiPPs and further highlights the structural novelty of cacaoidin.…”
Section: Figurementioning
confidence: 99%
“…Together, CypD activity prefers a dethiolated/dehydrated substrate (rather than hijacking the L-Cys19/L-Ser19functionalized intermediate) and tends to produce a D-AviCys-containing product. In fact, D-AviCys residue was found exclusively in related natural products that were characterized in stereochemistry 31,32 . The above results argue against the recent report by Zhang et al who failed to observe AviCys formation in the conversion of a Dhacontaining peptide and thus concluded that CypD has no cyclase activity 33 .…”
Section: Determination Of the Nature Of Cypd Substrate In Cyp Biosyntmentioning
confidence: 99%
“…Orthogonally, it has become a common strategy to look in underexplored geographical locations in order to find new and unique natural products. This has led natural products discovery efforts to interesting and exotic habitats, including tropical coral reefs [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], hypersaline lakes [ 54 ], the Arctic [ 55 ] and Antarctic [ 56 ], hydrothermal vents [ 57 ], and the deep sea [ 58 ]. In spite of the acknowledgement that sampling in new geographical locations can allow access to new natural products, there are few examples of systematically applying geographical knowledge in order to inform natural product discovery.…”
Section: Introductionmentioning
confidence: 99%